Asynchronous Bilateral Ovarian Torsion: Three Cases, Three Lessons - M. C. Lucchetti; C. Orazi; A. Lais; M. L. Capitanucci; P. Caione; H. Bakhsh (Case Reports in Pediatrics)
Background. Ovarian torsion (OT) is a serious condition, and delay in surgical intervention may result in loss of the ovary. Children and adolescents who have suffered from ovarian torsion may be at risk for asynchronous torsion of the contralateral ovary. Study objective. Three cases of asynchronous bilateral ovarian torsion were reported to analyse clinical history of three patients, to review the current literature, and to draw a conclusion for future treatment. Design. Case reports and review of the literature. Result. When a prepubertal girl presents with an ovarian torsion, several considerations have to be taken in account in order to preserve her future fertility; in particular, the pediatric surgeon/gynecologist has to preserve as much as possible the twisted ovary in addition to considering the fate of the contralateral ovary. Summary and Conclusions. Pelvic pain in a young girl has always raised the clinical suspect of an ovarian torsion; the possibility of asynchronous bilateral ovarian torsion is rare, but it is described in the literature and has catastrophic consequences; this condition has to be known and treated in the proper way by pediatric surgeons as well as by gynecologists in order to maximize the future fertility of the young patients.